WHEELING LAWS AND ORDINANCES, Act of Apr. 12, 1881 at 204, 206 (1891). - (:unkn) unknown (My University, 1881)
It shall be unlawful for any person to carry any slung shot, colt, or knucklers of lead, brass or other metal or material, or to carry about his person, hid from common observation, any pistol, dirk , bowie knife, or weapon of the like kind, without a permit in writing from the mayor so to do. It shall also be unlawful for any person or persons to sell or give away to a person not of age, any slung shot, colt, or knuckler or knucklers of lead, brass or other metal or material, or any pistol, dirk, bowie knife or weapon of the like kind."
Keywords: CARRY - CONCEALED